2005
DOI: 10.1073/pnas.0406278102
|View full text |Cite
|
Sign up to set email alerts
|

An interlocked dimeric parallel-stranded DNA quadruplex: A potent inhibitor of HIV-1 integrase

Abstract: We report on the NMR-based solution structure of the 93del d(GGGGTGGGAGGAGGGT) aptamer, a potent nanomolar inhibitor of HIV-1 integrase. This guanine-rich DNA sequence adopts an unusually stable dimeric quadruplex architecture in K ؉ solution. Within each 16-nt monomer subunit, which contains one A⅐(G⅐G⅐G⅐G) pentad sandwiched between two G⅐G⅐G⅐G tetrads, all G-stretches are parallel, and all guanines are anti with the exception of G1, which is syn. Dimer formation is achieved through mutual pairing of G1 of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 236 publications
(246 citation statements)
references
References 40 publications
6
232
1
2
Order By: Relevance
“…22 The present study has shown that this is not the case. The structure contains two single-residue double-chainreversal loops spanning three G-tetrad layers, a robust type of loop reported previously 15,28 that could play an important role in the folds of many G-quadruplexes 29 in K + solution. This quadruplex is remarkable in requiring the active participation of 18 out of the 22 nucleotides in the structural organization.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…22 The present study has shown that this is not the case. The structure contains two single-residue double-chainreversal loops spanning three G-tetrad layers, a robust type of loop reported previously 15,28 that could play an important role in the folds of many G-quadruplexes 29 in K + solution. This quadruplex is remarkable in requiring the active participation of 18 out of the 22 nucleotides in the structural organization.…”
Section: Discussionmentioning
confidence: 88%
“…This was anticipated, as the structure of a single-residue double-chain-reversal loop bridging three G-tetrad layers has been shown to be independent of the nature of the base in it. 28 Formation of the Watson-Crick A1•T12 base pair appears to be important for the structure, as the A1T mutation in the ck16 sequence altered the general fold (Figure 6b). The ck19 sequence containing the C11T mutation showed a doublings of imino proton peaks ( Figure 6b).…”
Section: Analysis Of Modified C-kit87up Sequencesmentioning
confidence: 99%
“…Residues of htel1U in the htel3I/htel1U quadruplex were numbered from 17 to 22 (Figure 1e). We refer to the htel3I/ htel1U quadruplex as a (3 + 1) quadruplex 13 assembly, because each G-tetrad contains three guanines from one strand and one guanine from the other strand. It should be noted that compared to the NMR spectra of the htel3I quadruplex the spectra of the htel3I/htel1U quadruplex showed the same number guanine and inosine imino protons, but fewer nonexchangeable protons (Figures 4, 5, and 7), consistent with the lack of an overhang tail in the htel3I/htel1U quadruplex (Figure 1d,e).…”
Section: Association Between Three-repeat and Single-repeat Human Telmentioning
confidence: 99%
“…13 The calculation protocol started with initial structures that were generated as sets of two strands (16-nt htel3I and 6-nt htel1U), randomized for all dihedral angles, and separated by space intervals of 50 Å. A total of 100 structures were embedded and optimized using the distance geometry simulated annealing protocol.…”
Section: Structure Calculationmentioning
confidence: 99%
“…These two activities suggest that quadruplexes may be new chemotherapeutic targets, and indeed this is being pursued by a variety of research groups 4 . In addition to serving as potential drug targets, some quadruplexes have been observed to possess therapeutic activity 5,6 . While most of these studies involve DNA quadruplexes, there has also been interest in the biological roles played by RNA quadruplexes 7 .…”
Section: Introductionmentioning
confidence: 99%